PENILAIAN KUALITAS DAN REDESAIN WEBSITE PT. WHIZZUP DIGITAL INDONESIA MENGGUNAKAN METODE WEBQUAL 4.0 - Michael Siahaan (2023)
The fast development of today's information and communication technologies mirrors the rising standard of living around the world. The use of technology across disciplines has benefited humanity by streamlining processes like information retrieval. The website is presently being used by many Indonesian businesses to introduce themselves to potential clients. Among the businesses that have promoted their products and services to the public through the website is Whizzup Digital Indonesia.. To see how the user's direct opinion of the Whizzup Digital Indonesia website, a pre-survey was conducted to obtain data that there were still users who were not satisfied with the Whizzup Digital Indonesia website and 70% of respondents suggested that the existing website be redesigned. Research with the title "Quality Assessment and Website Redesign of PT. Whizzup Digital Indonesia Using the Webqual 4.0 Method intends to assess the degree of customer (user) satisfaction with the Whizzup Digital Indonesia website, and revamp the Whizzup Digital Indonesia website. Primary data is analyzed to see whether the dimensions of website usage, the quality of website information, and the quality of website interactions are all realistic. Success in this research was measured by looking at how many people were happy with the look and functionality of current websites and how those websites were changed.